Rational Design of Three Dimensional Hollow Heterojunctions for Efficient Photocatalytic Hydrogen Evolution Applications - Pan, Jingwen; Wang, Dongbo; Wu, Donghai; Cao, Jiamu; Fang, Xuan; Zhao, Chenchen; Zeng, Zhi; Zhang, Bingke; Liu, Donghao; Liu, Sihang; Liu, Gang; Jiao, Shujie; et al. (Advanced science, 2024)
The efficiency of photocatalytic hydrogen evolution is currently limited by poor light adsorption, rapid recombination of photogenerated carriers, and ineffective surface reaction rate. Although heterojunctions with innovative morphologies and structures can strengthen built‐in electric fields and maximize the separation of photogenerated charges. However, how to rational design of novel multidimensional structures to simultaneously improve the above three bottleneck problems is still a research imperative. Herein, a unique Cu2O─S@graphene oxide (GO)@Zn0.67Cd0.33S Three dimensional (3D) hollow heterostructure is designed and synthesized, which greatly extends the carrier lifetime and effectively promotes the separation of photogenerated charges. The H2 production rate reached 48.5 mmol g−1 h−1 under visible light after loading Ni2+ on the heterojunction surface, which is 97 times higher than that of pure Zn0.67Cd0.33S nanospheres. Furthermore, the H2 production rate can reach 77.3 mmol g−1 h−1 without cooling, verifying the effectiveness of the photothermal effect. Meanwhile, in situ characterization and density flooding theory calculations reveal the efficient charge transfer at the p‐n 3D hollow heterojunction interface. This study not only reveals the detailed mechanism of photocatalytic hydrogen evolution in depth but also rationalizes the construction of superior 3D hollow heterojunctions, thus providing a universal strategy for the materials‐by‐design of high‐performance heterojunctions. Herein, a unique Cu2O─S@graphene oxide (GO)@Zn0.67Cd0.33S 3D hollow heterostructure is designed to realize the spatial separation and effective transfer of photogenerated charges. This study not only reveals the detailed mechanism of photocatalytic hydrogen evolution in depth through in situ characterization and theoretical calculations but also provides a universal strategy for the rational construction of excellent hollow heterojunctions.